Reasons of Singles for Being Single: Evidence from Brazil, China, Czech Republic, Greece, Hungary, India, Japan and the UK. (October 2021) - Apostolou, Menelaos; Birkás, Béla; da Silva, Caio Santos A.; Esposito, Gianluca; Hsu, Rafael Ming Chi S.; Jonason, Peter Karl; Karamanidis, Konstantinos; O, Jiaqing; Ohtsubo, Yohsuke; Putz, Ádám; Sznycer, Daniel; Thomas, Andrew G.; et al.
The current research aimed to examine the reasons people are single, that is, not in an intimate relationship, across eight different countries—Brazil, China, Czech Republic, Greece, Hungary, India, Japan, and the UK. We asked a large cross-cultural sample of single participants ( N = 6, 822) to rate 92 different possible reasons for being single. These reasons were classified into 12 factors, including one's perceived inability to find the right partner, the perception that one is not good at flirting, and the desire to focus on one's career. Significant sex and age effects were found for most factors. The extracted factors were further classified into three separate domains: Perceived poor capacity to attract mates, desiring the freedom of choice, and currently being in between relationships. The domain structure, the relative importance of each factor and domain, as well as sex and age effects were relatively consistent across countries. There were also important differences however, including the differing effect sizes of sex and age effects between countries.